Blood collection, platelet isolation and measurement of platelet count and size in mice—a practical guide - Katja Aurbach; Markus Spindler; Elizabeth J. Haining; Markus Bender; Irina Pleines (Platelets, 2019)
Inherited or acquired disorders of platelet production and function can result in thrombocytopenia and bleeding. Mouse models have proven useful for investigating the mechanisms that underlie these defects in humans. Precise methods for blood withdrawal, platelet isolation and measurement of platelet parameters are key for the generation of reproducible and conclusive data. Here, we provide three different protocols for mouse platelet isolation to encourage research knowledge transfer between experienced laboratories, while at the same time enabling less experienced researchers to implement a protocol that best suits their local expertise and equipment. We also address the issue that reported mouse platelet count and size vary considerably in the literature by investigating different factors that influence these important platelet parameters, namely: 1) genetic background and gender, 2) choice of analysis method (hematological analyzer or flow cytometry), 3) dilution of the blood sample and 4) choice of anticoagulant. The herein presented results and considerations may serve as a practical guide for both experienced and new researchers in the platelet field.